Diversity of novel archaeal viruses infecting methanogens discovered through coupling of stable isotope probing and metagenomics. (18th July 2022) - Ngo, Vuong Quoc Hoang; Enault, François; Midoux, Cédric; Mariadassou, Mahendra; Chapleur, Olivier; Mazéas, Laurent; Loux, Valentin; Bouchez, Théodore; Krupovic, Mart; Bize, Ariane
Abstract: Diversity of viruses infecting non‐extremophilic archaea has been grossly understudied. This is particularly the case for viruses infecting methanogenic archaea, key players in the global carbon biogeochemical cycle. Only a dozen of methanogenic archaeal viruses have been isolated so far. In the present study, we implemented an original coupling between stable isotope probing and complementary shotgun metagenomic analyses to identify viruses of methanogens involved in the bioconversion of formate, which was used as the sole carbon source in batch anaerobic digestion microcosms. Under our experimental conditions, the microcosms were dominated by methanogens belonging to the order Methanobacteriales ( Methanobacterium and Methanobrevibacter genera). Metagenomic analyses yielded several previously uncharacterized viral genomes, including a complete genome of a head‐tailed virus (class Caudoviricetes, proposed family Speroviridae, Methanobacterium host) and several near‐complete genomes of spindle‐shaped viruses. The two groups of viruses are predicted to infect methanogens of the Methanobacterium and Methanosarcina genera and represent two new virus families. The metagenomics results are in good agreement with the electron microscopy observations, which revealed the dominance of head‐tailed virus‐like particles and the presence of spindle‐shaped particles. The present study significantly expands the knowledge on the viral diversity of viruses of methanogens.